Insights Into Vaginal Bacterial Communities and Metabolic Profiles of Chlamydia trachomatis Infection: Positioning Between Eubiosis and Dysbiosis - Parolin, Carola; Foschi, Claudio; Laghi, Luca; Zhu, Chenglin; Banzola, Nicoletta; Gaspari, Valeria; D’Antuono, Antonietta; Giordani, Barbara; Severgnini, Marco; Consolandi, Clarissa; Salvo, Melissa; Cevenini, Roberto; et al. (Frontiers in Microbiology, 2018)
The vaginal microbiota plays a crucial role in maintaining the health and functioning of the female genital tract, preventing the colonization of urogenital pathogens and sexually transmitted infections. In this study, we characterized the vaginal bacterial communities and the metabolome associated to Chlamydia trachomatis infection (CT: 20 women), compared to healthy condition (H: 22 women) and bacterial vaginosis (BV: 19 women). A microarray-based tool (VaginArray), implemented with a real-time PCR for Gardnerella vaginalis, was used to determine the vaginal bacterial composition, whereas the metabolic profiles were assessed by a proton-based nuclear magnetic resonance (1H-NMR) spectroscopy. CT infection was characterized by bacterial and metabolic signatures similar to healthy condition, even though higher amounts of Lactobacillus iners, as well as depletion of some amino acids, biogenic amines and succinate marked CT infection. Moreover, the frequency of Lactobacillus crispatus was higher in asymptomatic CT-positive patients than in women with CT-correlated symptoms. We also confirmed the marked differences in the microbiome and metabolome between healthy and BV-affected women. In conclusion, we highlighted microbial and metabolic peculiarities of the vaginal ecosystem in the case of CT infection, even though further studies are needed to understand if the observed alterations precede the infection onset or if the pathogen itself perturbs the vaginal environment.